Vitronectin, Integrin Vitronectin Receptor Other Biochemical Markers to Assess the Development of Liver Cirrhosis - Huda Jaber Waheed (Journal of Global Pharma Technology, 2017)
Aim of study: To evaluate some fibrosis markers such as vitronectin, serum vitronectin receptor (VNR) and the amino terminal propeptide of type III procollagen (P-III-P) in the sera of liver cirrhosis patients and to monitor the behavior of these markers in disease progression. Material and Methods: About (60) volunteer participated in current study; 30 patients and 30 patients. The patients were divided according to severity of the disease by Child-Pugh Score to three classes: (10) patients class A, (10) class B patients and (10) class C. Procollagen III peptide, serum vitronectin and vitronectin receptor were measured in serum by ELISA. Results: A Significant increases were found in serum vitronectin, receptor and sP-III-P in all patients' sub-groups when compared to control. VNR seems to detect early liver cirrhosis and distinguish between patients (A and B classes) and advanced disease with cirrhosis. Conclusion: According to our data, the area under curve of serum VNR is greater than vitronectin and Sp-III-P so it can be act as a marker of liver cirrhosis and also could be used to monitor the severity of disease.